A task force for diagnosis and treatment of people with Alzheimer’s disease in Latin America - Lopera, Francisco; Custodio, Nilton; Rico-Restrepo, Mariana; Allegri, Ricardo F.; Barrientos, José Domingo; Garcia Batres, Estuardo; Calandri, Ismael L.; Calero Moscoso, Cristian; Caramelli, Paulo; Duran Quiroz, Juan Carlos; Jansen, Angela Marie; Mimenza Alvarado, Alberto José; et al. (Frontiers in Neurology, 2023)
Alzheimer’s disease (AD) represents a substantial burden to patients, their caregivers, health systems, and society in Latin America and the Caribbean (LAC). This impact is exacerbated by limited access to diagnosis, specialized care, and therapies for AD within and among nations. The region has varied geographic, ethnic, cultural, and economic conditions, which create unique challenges to AD diagnosis and management. To address these issues, the Americas Health Foundation convened a panel of eight neurologists, geriatricians, and psychiatrists from Argentina, Brazil, Colombia, Ecuador, Guatemala, Mexico, and Peru who are experts in AD for a three-day virtual meeting to discuss best practices for AD diagnosis and treatment in LAC and create a manuscript offering recommendations to address identified barriers. In LAC, several barriers hamper diagnosing and treating people with dementia. These barriers include access to healthcare, fragmented healthcare systems, limited research funding, unstandardized diagnosis and treatment, genetic heterogeneity, and varying social determinants of health. Additional training for physicians and other healthcare workers at the primary care level, region-specific or adequately adapted cognitive tests, increased public healthcare insurance coverage of testing and treatment, and dedicated search strategies to detect populations with gene variants associated with AD are among the recommendations to improve the landscape of AD.